2010
DOI: 10.1002/hbm.20882
|View full text |Cite
|
Sign up to set email alerts
|

Comparing 3 T and 1.5 T MRI for tracking Alzheimer's disease progression with tensor‐based morphometry

Abstract: A key question in designing MRI-based clinical trials is how the main magnetic field strength of the scanner affects the power to detect disease effects. In 110 subjects scanned longitudinally at both 3.0 and 1.5 T, including 24 patients with Alzheimer's Disease (AD) [74.8 ± 9.2 years, MMSE: 22.6 ± 2.0 at baseline], 51 individuals with mild cognitive impairment (MCI) [74.1 ± 8.0 years, MMSE: 26.6 ± 2.0], and 35 controls [75.9 ± 4.6 years, MMSE: 29.3 ± 0.8], we assessed whether higher-field MR imaging offers hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 69 publications
5
78
0
Order By: Relevance
“…In volumetric studies, several groups have analyzed the effects of different scanners on cross-sectional or longitudinal morphometric results [Briellmann et al, 2001;Dickerson et al, 2008;Ewers et al, 2006;Fennema-Notestine et al, 2007;Fjell et al, 2009;Han et al, 2006;Ho et al, 2010;Huppertz et al, 2010;Jovicich et al, 2009;Kruggel et al, 2010;Meda et al, 2008;Moorhead et al, 2009;Pardoe et al, 2008;Schnack et al, 2004;Stonnington et al, 2008;Walhovd et al, 2009]. Usually, inter-scanner variability of volumetric measures is larger than intra-scanner variability.…”
Section: Discussionmentioning
confidence: 99%
“…In volumetric studies, several groups have analyzed the effects of different scanners on cross-sectional or longitudinal morphometric results [Briellmann et al, 2001;Dickerson et al, 2008;Ewers et al, 2006;Fennema-Notestine et al, 2007;Fjell et al, 2009;Han et al, 2006;Ho et al, 2010;Huppertz et al, 2010;Jovicich et al, 2009;Kruggel et al, 2010;Meda et al, 2008;Moorhead et al, 2009;Pardoe et al, 2008;Schnack et al, 2004;Stonnington et al, 2008;Walhovd et al, 2009]. Usually, inter-scanner variability of volumetric measures is larger than intra-scanner variability.…”
Section: Discussionmentioning
confidence: 99%
“…In a strictly signal-to-noise comparison study, Fushimi et al 24 reported no significant differences in signal-to-noise ratios between 1.5T and 3T in multisection images with a 0-mm gap. Applying tensor brain morphometry and Structural Image Evaluation Using Normalization of Atrophy algorithms to ADNI-1 1.5T and 3T data, Ho et al 26 reported no significant advantage of 3T over 1.5T for detecting 1-year whole-brain atrophy rates. Perhaps most importantly, 2 groups compared the performance of their automated multiatlas hippocampal segmentation techniques at 1.5T and 3T in small samples derived from ADNI-1.…”
Section: Discussionmentioning
confidence: 99%
“…2427 One tensor-based morphometry whole-brain study reported that analyses of 1.5T and 3T Alzheimer’s Disease Neuroimaging Initiative (ADNI) data from the same subjects did not differ statistically in detecting neurodegenerative changes during 12 months. 26 Hippocampal volumes extracted from the same study cohort at 1.5T and 3T showed only 3.2% test-retest variability. 25 Similar results were reported for manual segmentations in 8 healthy subjects with 1.5T and 3T scans in an epilepsy study.…”
mentioning
confidence: 83%
“…One of the aims of ADNI 1 was to compare structural MRI measures at 1.5T vs 3T to determine if field strength had a significant impact on quantitative measures that were relevant to AD clinical trials. ADNI investigators found that the two field strengths were roughly comparable with no major drawbacks unique to either [11, 12]. Because of greater signal to noise and the greater flexibility for more advanced scanning techniques at 3T, ADNI GO/2 was conducted entirely at 3T [3].…”
Section: Accomplishments Of the Adni Mri Core To Datementioning
confidence: 99%